Farms’ structural adjustment to the increasing competitive pressure: specialization vs. de-specialization in Italian agriculture - Cardillo, Concetta; Fusco, Daniela; Moretti, Valerio; Russo, Carlo (Italian Review of Agricultural Economics, 2016)
The paper provides an application of micro-data statistical analysis for agricultural economics studies. We use data from the 2000 and 2010 Censuses to build a short, two-year panel of 823.771 farms and we used the panel to describe specialization in Italian agriculture. We classified Italian farms into four groups according to their adoption of specialized Type of Farming (TOF) in 2000 and 2010 or de-specialized TOF in both surveys, or the change from a specialized to a de-specialized TOF or vice versa. The degree of specialization in Italian agriculture increased over the decade and the result was driven mostly by a relevant shift toward specialization of farms located in the mountain areas of central and southern Italy. We also found an association between the age structure of the family workforce and the choice of adopting a specialized TOF.